Silent cities visualization. The case study of the Main Cemetery of Padua & the Cemetery Island of San Michele in Venice: preliminary reflections - David Navarro Moreno; Maria Jose Muñoz Mora; Stefano Zaggia (Disegnare con)
The complexity of cultural management processes in historical cities calls for methods and tools to improve the understanding of the urban realm and underlying relationships and connections. In this sense, visualization as a tool for analysis, exploration, and communication has become a driving force in the task of unravelling the complex urban fabrics that form historical cities. At present, there are several research projects which have been developed on the visualization of some historical cities. Unfortunately, up to now, many of these projects have focused on the study of the city of the living, relegating the city of the dead to the background. However, it should be remembered that there has not always been this distinction between the spaces assigned to one or the other, but for centuries the city has been shared by both. DOI: https://doi.org/10.20365/disegnarecon.21.2018.4